Facile ZIF‐8 functionalized hierarchical micronanofiber membrane for high‐efficiency separation of water‐in‐oil emulsions - Xu, Si; Ren, Long‐Fei; Zhou, Qing; Bai, Hongwei; Li, Jun; Shao, Jiahui (Journal of applied polymer science, 2018)
ABSTRACT The efficient separation and recovery of oil from water‐in‐oil emulsion poses a great challenge because of the rapid development of the petrochemical industry throughout the world. In this study, a facile method to develop a ZIF‐8 functionalized hierarchical micronanofiber membrane for high‐efficiency oil/water separation was investigated. The electrospun PVDF/ZnO membrane was made, on which ZIF‐8 crystal seeds were then created with the revitalizing step and expanded in the growth step, and finally functionalized hierarchical micronanofiber PVDF‐g‐ZIF‐8 membrane was obtained. Results showed that oleophilic ZIF‐8 crystals on the surface of PVDF membrane dramatically increased the wettability of oil and tuned PVDF membrane from olephobicity to oleophilicity. The hydrophobic/lipophilic PVDF‐g‐ZIF‐8 membrane with a water contact angle up to 158° and a toluene contact angle down to 0° provides its separation efficiency for water‐in‐oil emulsion of 92.93% in an environmentally friendly and energy‐saving manner. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2018, 135, 46462.